Parallel Concerted Evolution of Ribosomal Protein Genes in Fungi and Its Adaptive Significance. (7th October 2019) - Mullis, Alison; Lu, Zhaolian; Zhan, Yu; Wang, Tzi-Yuan; Rodriguez, Judith; Rajeh, Ahmad; Chatrath, Ajay; Lin, Zhenguo
Abstract: Ribosomal protein (RP) genes encode structural components of ribosomes, the cellular machinery for protein synthesis. A single functional copy has been maintained in most of 78–80 RP families in animals due to evolutionary constraints imposed by gene dosage balance. Some fungal species have maintained duplicate copies in most RP families. The mechanisms by which the RP genes were duplicated and maintained and their functional significance are poorly understood. To address these questions, we identified all RP genes from 295 fungi and inferred the timing and nature of gene duplication events for all RP families. We found that massive duplications of RP genes have independently occurred by different mechanisms in three distantly related lineages: budding yeasts, fission yeasts, and Mucoromycota. The RP gene duplicates in budding yeasts and Mucoromycota were mainly created by whole genome duplication events. However, duplicate RP genes in fission yeasts were likely generated by retroposition, which is unexpected considering their dosage sensitivity. The sequences of most RP paralogs have been homogenized by repeated gene conversion in each species, demonstrating parallel concerted evolution, which might have facilitated the retention of their duplicates. Transcriptomic data suggest that the duplication and retention of RP genes increased their transcript abundance. Physiological data indicate that increased ribosome biogenesis allowed these organisms to rapidly consume sugars through fermentation while maintaining high growth rates, providing selective advantages to these species in sugar-rich environments.